Endotoxins in baled cottons and airborne dusts in textile mills in the People's Republic of China. - Olenchock, S A (1983)
Bulk cotton samples and airborne vertical elutriated cotton dusts were obtained from textile mills in Shanghai, People's Republic of China. Analysis of endotoxin contents revealed that baled cottons which were grown in different countries varied in endotoxin contamination. The two textile mills, which operated at similar overall airborne dust levels, differed markedly in the levels of airborne endotoxins. The data suggest that the biological activity or "toxicity" of airborne cotton dusts may not be correlated directly with gravimetric dust levels.